2018
DOI: 10.3390/md16040106
|View full text |Cite
|
Sign up to set email alerts
|

A Potential Adjuvant Agent of Chemotherapy: Sepia Ink Polysaccharides

Abstract: Sepia ink polysaccharide (SIP) isolated from squid and cuttlefish ink is a kind of acid mucopolysaccharide that has been identified in three types of primary structures from squid (Illex argentinus and Ommastrephes bartrami), cuttlefish Sepiella maindroni, and cuttlefish Sepia esculenta ink. Although SIP has been proved to be multifaceted, most of the reported evidence has illuminated its chemopreventive and antineoplastic activities. As a natural product playing a role in cancer treatment, SIP may be used as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 54 publications
0
8
0
2
Order By: Relevance
“…By monomeric units, they can be either homo-or heteroglycans, and by charge, neutral or anionic. Polysaccharides are also classified according to their source: (i) starch, cellulose, and exudate gums from plants; (ii) alginates and galactans from algae; (iii) chitin, chitosan, and glycosaminoglycans from animals; (iv) dextran, pullulan and, gellan and xanthan gums from microorganisms; and (v) glucans from mushrooms (Friedman, 2016;Choong et al, 2018;Li et al, 2018b;Yadav and Karthikeyan, 2019).…”
Section: Natural Polysaccharidesmentioning
confidence: 99%
“…By monomeric units, they can be either homo-or heteroglycans, and by charge, neutral or anionic. Polysaccharides are also classified according to their source: (i) starch, cellulose, and exudate gums from plants; (ii) alginates and galactans from algae; (iii) chitin, chitosan, and glycosaminoglycans from animals; (iv) dextran, pullulan and, gellan and xanthan gums from microorganisms; and (v) glucans from mushrooms (Friedman, 2016;Choong et al, 2018;Li et al, 2018b;Yadav and Karthikeyan, 2019).…”
Section: Natural Polysaccharidesmentioning
confidence: 99%
“…Aubourg et al, [15] đã xác định các chất chiết xuất từ da mực Dosidicus gigas với dung môi ethanol là nguồn chất chống oxy hóa hứa hẹn để làm chậm quá trình oxy hóa lipid của cá. Nghiên cứu của Li et al, [16] cho thấy chất chiết từ mô của mực ống cải thiện khả năng chống oxy hóa của lá lách ở động vật. Tuy nhiên, các nghiên cứu khảo sát về các chất hoạt sinh học của động vật thân mềm và vai trò của chúng như chất kháng oxy hóa ở các loài mực ở nước ta còn khá hạn chế.Trong nghiên cứu này, chúng tôi khảo sát hoạt tính kháng oxy hóa ở một số loài mực ở Khánh Hòa để xác định các hợp chất có tầm quan trọng trong y sinh.…”
Section: Giới Thiệuunclassified
“…Kết quả điện di cũng thể hiện các thành phần protein với các trọng lượng phân tử khác nhau. Nghiên cứu của Vate et al, [16] cho thấy melanin trong mực Loligo formosana các phần có MW dưới 3 kDa có các hoạt động chống oxy hóa cao nhất (p < 0,05), do đó có thể đóng vai trò là chất chống oxy hóa tự nhiên để làm chậm quá trình oxy hóa lipid trong các sản phẩm thực phẩm. Như vậy khả năng kháng oxi hóa của chất chiết từ túi mực nang và mực ống trong khảo sát này có thể chủ yếu là do melamin tạo nên.…”
Section: Thành Phần Protein Của Các Cao Chiết Methnolunclassified
“…It was demonstrated that Trametes versicolor (Synn. Coriolus versicolor) polysaccharides, fucoidan , and sepia Ink polysaccharides could be applied as adjuvant therapies of cancer, which usually possess low levels of toxicity and have high safety ( 11 13 ). Furthermore, polysaccharides could promote the recovery of patients with cancer ( 14 , 15 ).…”
Section: Introductionmentioning
confidence: 99%